Design of a 40nm CMOS instrumentation amplifier for biomedical applications - Tan, Lucas Wen Yu (Nanyang Technological University, 2024)
This project explores using the differential difference amplifier (DDA) architecture to design an instrumentation amplifier that can be used in biomedical applications. DDAs are used in biomedical applications such as biosignal acquisition and neural signal recording. This project discusses the DDA as an alternative to the traditional operational amplifier. The designed amplifier has high gain, high input impedance, and provides good common-mode rejection ratio. The circuit has simple circuitry and low power dissipation. It has a a low quiescent current with a single supply of 1.2V.